ADOPTION OF BIOFORTIFIED CASSAVA AMONG FARMERS IN SOUTH WEST NIGERIA: A BINARY LOGIT ANALYSIS OF THE DETERMINANTS - Omowunmi Veronica AYODELE; Oluwatosin Olusegun FASINA; Oluwatoyin Faramade OSUNDAHUNSI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The adoption of agricultural technologies is a vital strategy in addressing food security and improving households’ nutrition. This study xamined the determinants of adoption of biofortified cassava among farmers in South West Nigeria using a binary logistic regression model.Primary data through administration of structured interview were obtained from 396 respondents which were selected using a multistage samplng technique. Descriptive analysis of the socio-economic characteristics analysis showed the mean of 46.9 years, 1.8ha, 20.0 years and 238,693.18 for age, farm size, years of experience and income of the respondents respectively. Most (68.9%) of the respondents were males,77.0% were primarily farmers, 90.2% were literate, 87.1% were married, 86.1% had group membership while 89.4% had access to extension ervices. There were low levels of awareness of the benefits of biofortified cassava and cosmopliteness of the respondents. The Binary ogistic regression model result revealed that adoption of biofortified cassava was influenced by increase in awareness, perception, incomefrom cassava, marital status and a decrease in age. It is therefore recommended that increase in awareness, income, and positive perceptionand younger farmers should be targeted when channeling a course for adoption of a new technology.